Innovations in the field of state and legal regulation of socio-economic activity in Modern times - Nebratenko Gennady; Studenikina Svetlana; Kazantseva Olga (E3S Web of Conferences, 2020)
The proposed article is designed to prove the importance of forming a national economy based on the domestic experience of state and legal regulation, taking into account the realities of the development of international relations, as well as threats arising at the interstate and national levels. At the same time, each state has its own economic system associated with the categories of "economic sovereignty" and "state sovereignty". For that reason, the comparative methodology is reflected in the consideration of the problems stated in the proposed article. The authors proved the importance of financial and economic support of Russia as a social state in order to develop its demographic potential-the most important segment of the national economy construction. In conclusion, the opinion was expressed that ensuring the economic sovereignty of the Russian Federation through the construction of the national economy will have a positive impact on the level of national security.